Differences in medical students’ attitudes to academic misconduct and reported behaviour across the years—a questionnaire study - Rennie, S. C. (Journal of medical ethics, 2003)
Objectives: This study aimed to determine attitudinal and self reported behavioural variations between medical students in different years to scenarios involving academic misconduct. Design: A cross-sectional study where students were given an anonymous questionnaire that asked about their attitudes to 14 scenarios describing a fictitious student engaging in acts of academic misconduct and asked them to report their own potential behaviour. Setting: Dundee Medical School. Participants: Undergraduate medical students from all five years of the course. Method: Questionnaire survey. Main measurements: Differences in medical students’ attitudes to the 14 scenarios and their reported potential behaviour with regards to the scenarios in each of the years. Results: For most of the scenarios there was no significant difference in the response between the years. Significant differences in the responses were found for some of the scenarios across the years, where a larger proportion of year one students regarded the scenario as wrong and would not engage in the behaviour, compared to other years. These scenarios included forging signatures, resubmitting work already completed for another part of the course, and falsifying patient information. Conclusion: Observed differences between the years for some scenarios may reflect a change in students’ attitudes and behaviour as they progress though the course. The results may be influenced by the educational experience of the students, both in terms of the learning environment and assessment methods used. These differences may draw attention to the potential but unintentional pressures placed on medical students to engage in academic misconduct. The importance of developing strategies to engender appropriate attitudes and behaviours at the undergraduate level must be recognised.